Spontaneous Acute Subdural Hematoma Associated with Cerebral Cortical Arteriovenous Fístula: Case Report and Literature Review. - Cabrera, Felipe; Villanueva, Pablo; Andino, Yanina (Revista Argentina de Neurocirugía, 2024)
Spontaneous subdural hemorrhages are not very frequent. Among them, ones due to vascular fistula are even less in frequency and a real challenge for the health team. Just a few cases worldwide allow to perform some guidelines about clinical presentation, diagnostic algorithms and specific treatment. A bibliographic revision has been made and a new case is published, aiming to provide useful information to suspect this pathology and propose a possible diagnostic and therapeutic approach.
Keywords: spontaneous subdural hematoma - cerebral arteriovenous fistulae